Fragmentation Analysis For Scalable Wireless Local Area Networks - Minhaj Ahmad Khan, (Journal of Basic & Applied Sciences, 2021)
Wireless networks are being deployed widely to provide network connectivity without requiring the web of physical wires. A collection of a small number of workstations connected using a wireless network forms a wireless local area network (WLAN) that follows the IEEE 802.11 standard. In a WLAN, the communication takes place using packets whose sizes may vary and have a significant impact on the delay incurred during transmission. In this regard, fragmentation may play a vital role in reducing the delay for efficient transmission across the network. This paper analyzes the performance of WLANs with respect to the packet fragmentation. We simulate three network scenarios having 4, 8 and 12 wireless workstations respectively. The scenarios are simulated using OPNET IT Guru Academic Edition v 9.1 while incorporating a peer-to-peer (P2P) based communication model for each scenario. We compare the performance of non-fragmented and fragmented communication in terms of network delay and throughput. Our results show that the fragmentation minimizes the delay and increases the throughput, however its impact is highly dependent on the size of the underlying network.